The management of forecasting in business decisions: An empirical analysis (2018)
Forecast management is a strategic issue in companies, who choose a method or the combination of several of them for comparison and use in decision making. However, it was possible to verify the relative lack of information and analysis that exists around the way in which they use it as a strategic planning tool for decision making. The research is carried out in Bogotá (Colombia), through the application of a structured survey. It is concluded that companies do not have an articulated forecasting process for decision making; they agree on the type of variables they predict and on the linear methods and computer programs they use, but there are differences when compared by company size. © 2018, revistaESPACIOS.com.